Miss Pym disposes : with a new introduction by Robert Barnard - Tey, Josephine, 1896 or 1897-1952 (Scribner Paperback Fiction, 1998)
To Lucy Pym, author of a best-seller on Psychology, the atmosphere at the college where she is lecturing is heavy with tension. Beneath the so normal surface run sinister undercurrents of rivalry and jealousy. Then comes tragedy. An accident? Or is it murder? Respectable, law-abiding Miss Pym discovers some vital evidence - but should she reveal it?